1997
DOI: 10.1302/0301-620x.79b5.6749
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Hemipelvis after the Excision of Malignant Tumours

Abstract: We treated 35 patients with primary malignant tumours of the periacetabular area by resection and prosthetic reconstruction of the defect. At a mean follow-up of 84 months, 15 patients (43%) were free from disease. The most common complications were deep infection (26%), local recurrence (24%) and recurrent dislocation of the hip (17%). The surviving patients achieved an average of 70% of their premorbid function. This method of reconstruction has a high morbidity and should be performed only at specialist cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
87
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 11 publications
8
87
1
1
Order By: Relevance
“…Dislocation and aseptic loosening of endoprostheses are other major postoperative complications. The rates of dislocation (16%) and aseptic loosening (8%) in the present series were also comparable to other reported series: 2.5% to 17% for dislocation [1,11,14,24,27,[36][37][38]] and 3.7% to 25% for aseptic loosening of implants [11,14,21,27,38]. Four patients sustained dislocations caused by violent falls despite the use of a constrained joint mechanism, three of whom also had concomitant deep infection.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Dislocation and aseptic loosening of endoprostheses are other major postoperative complications. The rates of dislocation (16%) and aseptic loosening (8%) in the present series were also comparable to other reported series: 2.5% to 17% for dislocation [1,11,14,24,27,[36][37][38]] and 3.7% to 25% for aseptic loosening of implants [11,14,21,27,38]. Four patients sustained dislocations caused by violent falls despite the use of a constrained joint mechanism, three of whom also had concomitant deep infection.…”
Section: Discussionsupporting
confidence: 89%
“…hemipelvic prostheses [1,18,27,36,37], 11% to 24% in modular-type hemipelvic prostheses [11,14,24,38], and 8% to 60% in allograft reconstruction [2,22,23,26,39]. To reduce the risk of postoperative deep infection, we need to adopt intraoperative repeated and meticulous ultrasonic irrigation, routine use of antibiotic-loading bone cement, application of muscle/or musculocutaneous flap, and twostaged reconstruction after tumor resection followed by a ''Reconstruction cup'' (C-THA) endoprosthesis 55% (30%-80%) 32%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 20% infection rate in our series of patients is lower than reported rates in some series [3,4,18,26,27,36,39,41,45,46] and greater or comparable to the experience reported in other studies [1,8,12,13,19,20,29,30,38] ( Table 3). The overall infection rate in many series varied from 10% to 47% after internal hemipelvectomy [1, 3, 4, 8, 10, 12, 13, 18-20, 23, 25-27, 29, 30, 34, 36, 38-41, 45, 46], whereas it ranged from 11% to 38% in patients who had resection and endoprosthetic reconstruction [1,3,12,19,20,26,27,36,45,46]. Abudu et al [3] reported a 26% infection rate in a series of 35 patients undergoing endoprosthetic reconstruction with saddle prostheses.…”
Section: Discussionsupporting
confidence: 80%
“…However, hemipelvic reconstruction after sarcoma resection is critical and many methods for the approach exist, such as massive allograft [1][2][3][4], autoclaved autograft [5,6], custom-made endoprosthesis combined with hip arthroplasty [7][8][9], modular saddle prosthesis [9][10][11][12], and modular hemipelvic endoprosthesis [13,14]. The modular hemipelvic prosthesis is a new design that can be easily used in surgery and features flexible sizes.…”
Section: Introductionmentioning
confidence: 99%